SECURITY MANAGEMENT SYSTEM AND OCCUPATIONAL HEALTH IN SOUTHERN COUNTRIES - Abu Bakar, Junaidy (International Business Education Journal, 2013)
The study attempts to explain the occupational safety and health management system that has been practices in a few southern countries and also to analyze a case study of Japan’s management system in preventing industrial accidents. The discussion presents the issues of the industrial accidents phenomenon in the local and global degree. It is revealed that the industrial accidents phenomenon has been a serious phenomenon in Malaysia due to organizational factors or the factor of the individual behavior. The study also discovers that the effectiveness of Japan’s management practice in handling industrial accidents phenomenon through its “working culture” as based on Kaizen concept of attitude has successfully led the countries to their peak in the world. Thus, this study is significant not only to highlight the seriousness of the industrial accidents in Malaysia and other southern countries, but also to help lessen employees’ burden and trauma by practicing a more systematic safety management in International Labor Organization (ILO), as well as by upholding Japan to be the role model in the implementation of industrial safety programs, specially occupational safety and health management system (OHMS) programs.